2018
DOI: 10.1056/nejmp1800606
|View full text |Cite
|
Sign up to set email alerts
|

Accessibility of Medical Diagnostic Equipment — Implications for People with Disability

Abstract: Under Attorney General Jeff Sessions, the U.S. Department of Justice (DOJ) has inactivated or rescinded numerous rules and guidelines issued by prior administrations, sometimes attracting considerable public attention in the process. Little noticed, however, was a decision by the DOJ on December 26, 2017, to formally withdraw four Advance Notices of Proposed Rulemaking related to Titles II and III of the Americans with Disabilities Act (ADA), including rulemaking that addressed making medical diagnostic equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…Although the current study did not investigate the reasons for such disparities, previous studies have suggested several factors as barriers to breast cancer screening related to disability: 1) system factors (eg, inaccessible facilities or equipment, transportation problems, insurance coverage or economic issues); 2) provider factors (eg, poor knowledge of disability, negative stereotyping and social misconceptions, and failure to recommend preventive services); and 3) patient factors (eg, disability‐specific barriers [eg, communication], competing health issues, lack of awareness or knowledge, misperceptions regarding screening, and lack of a usual source of care).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the current study did not investigate the reasons for such disparities, previous studies have suggested several factors as barriers to breast cancer screening related to disability: 1) system factors (eg, inaccessible facilities or equipment, transportation problems, insurance coverage or economic issues); 2) provider factors (eg, poor knowledge of disability, negative stereotyping and social misconceptions, and failure to recommend preventive services); and 3) patient factors (eg, disability‐specific barriers [eg, communication], competing health issues, lack of awareness or knowledge, misperceptions regarding screening, and lack of a usual source of care).…”
Section: Discussionmentioning
confidence: 97%
“…However, those with severe physical disabilities demonstrated markedly lower participation rates. Mammography requires women to stand while undergoing the procedure; however, women with major lower extremity mobility issues would have difficulty standing and being positioned for examination . Similarly, severe visual or hearing disabilities might limit access to screening information and could be a significant barrier for communication with health care professionals, unlike mild visual or hearing difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…The main drivers of complicated appendicitis are considered to be delayed diagnosis and treatment. Although we could not establish the reasons for late diagnosis and treatment in our disabled group, barriers to healthcare have been suggested in previous studies, including access to facilities, equipment, and transportation ( 7 , 28 , 29 ). Accessing medical facilities is more difficult for disabled than non-disabled people due to physical and transportation problems; this leads to late diagnosis or treatment of appendicitis, which in turn increases the likelihood of complicated appendicitis developing.…”
Section: Discussionmentioning
confidence: 80%
“…USPSTF suggests that if CBE is the only screening test available, as in some low-resource countries, it may be reasonable for screening (U.S. Preventive Services Task Force, 2013). More than 30 years since enacting the Americans with Disabilities Act (ADA), accessible medical diagnostic equipment, including that for mammography, is not universally available across U.S. health care settings (Iezzoni & Pendo, 2018). However, in the United States, with its strong resources, defaulting to CBE-unless there is a true reason women cannot be accommodated-could represent inequitable care, which would be against the ADA's requirements that women with disability receive equal quality of care.…”
Section: Discussionmentioning
confidence: 99%